The power model of juvenile justice - Swart, Stanley L. (American journal of criminal justice, 1980)
The author first identifies those characteristics which distinguish the juvenile justice system from its more widelypublicized counterpart, the criminal justice system. He next demonstrates how many textbooks in this area fail to portray adequately the uniqueness of juvenile justice. He concludes by developing and explaining the “Power Model,” which more accurately describes the juvenile justice system.